Kerk en teologie in die jaar nul - Vos, Casparus Johannes Adam (Verbum et ecclesia, 2000)
Church and theology in the year nil In this article, attention is given to the significance of a singular faculty of theology being realised. Furthermore, the influence on the dynamic relation between church and society is considered. From here, in the closing movement, guidelines are presented for an energetic life-force theology. The characteristics of such a theology are: a theology of working with the Word and words; the nomad; a theology for contemplating life; ethical conduct; and a theology that encourages the appreciation for the incredible.